Patients' attitudes and perceptions towards treatment of hypothyroidism in general practice: an in-depth qualitative interview study. Issue 2 (2017) - Dew, Rosie; King, Kathryn; Okosieme, Onyebuchi E; Pearce, Simon; Donovan, Gemma; Taylor, Peter; Leese, Graham; Hickey, Janis; Razvi, Salman; Dayan, Colin; Wilkes, Scott
No abstract available